Australia's DIGI Code: what can we learn from the EU experience?. Issue 3 (3rd July 2022) - Hurcombe, Edward; Meese, James
ABSTRACT: Disinformation and misinformation on social media platforms are growing regulatory concerns for governments. In this paper, we examine Australia's DIGI Code of Practice (CoP). The CoP is a voluntary set of commitments to address false content on platforms that is overseen by Australia's digital media industry. It was established in response to a federal government directive. We evaluate the DIGI CoP by comparing it to the code it was partially based on: the EU's Code of Practice on Disinformation (EU CPD). The EU CPD also attempted voluntary regulation, and yet the EU is now moving towards a strengthened CPD. While the DIGI CoP improves upon the original EU CPD, the original version had limited accountability measures and notable content exclusions. We conclude by discussing a recent review of the CoP, suggesting that Australia will also strengthen regulation in this area. Lastly, we address ongoing tensions around media freedom and accountability.